A guide to Aboriginal and Torres Strait Islander histories and cultures - Goodwin, Jo. (Deakin West, A.C.T. : c)
In Australia, we have two distinct peoples who are Indigenous to our nation: Aboriginal peoples and Torres Strait Islander peoples. Whether or not you are beginning or continuing your learning on how to best include and explore Aboriginal and Torres Strait Islander cultures with young children, it is your commitment, time, values and attitudes that will progress these ideas. An ongoing commitment to progressing reconciliation with young children can be achieved through building positive relationships, demonstrating respect and creating opportunities with Aboriginal and/or Torres Strait Islander peoples and the broader community in which you live and work.
Includes bibliographical references.
Keywords: Cultural competence; Aboriginal culture; Cultural awareness; Cultural literacy